Comment les enseignantes et enseignants issus de l’immigration comparent-ils la conception de l’enseignement : en faculté d’éducation manitobaine et en stage en milieu francophone minoritaire lors de leur formation initiale par rapport à celle qu’ils ont pu connaitre dans leur pays d’origine ? - Lupien, Claudine (Canadian Journal of Education/Revue canadienne de l’éducation, 2023)
This qualitative research study is based on a series of 10 semi-structured interviews with graduates of the Faculty of Education at the Université de Saint-Boniface, Manitoba, Canada, who were internationally educated during their pre-university or university studies. This study focuses on these graduates’ perceptions in relation to several themes, including their conception of teaching. Since the scholastic landscape is in full evolution due in part to migratory flows, the professional integration of future internationally educated immigrant teachers can present several challenges. This study gives voice to immigrant teachers in order to better understand the cultural discontinuities related to their conception of teaching. Avenues for reflection and action aimed at better equipping students educated outside of Canada and education faculties with regards to their knowledge of the conception of teaching in Canada will also be discussed.